TINJAUAN PEMBERDAYAAN PEREMPUAN PRASEJAHTERA PRODUKTIF PELAKU UMKM TERHADAP PROGRAM FASILITATOR PENDAMPING ACCESS TO KNOWLADGE REMOTE SITE PEDESAAN - Israni, Sherli (Irtifaq, 2023)
This article discusses the review of the empowerment of productive underprivileged women of UMKM actors against the facilitator access to knowledge remote site program (11 villages scattered in Jogroto district, Jombang Regency). Productive underprivileged communities of micro, small, and medium enterprises (UMKM) are the biggest drivers and contributors to Indonesia’s economic growth. However, these UMKM actors often have difficulty getting market access and access to knowledge, this is the background for the establishment of the facilitator access to knowledge remote site program by PT. Bank BTPN Syariah Tbk. The facilitator access to knowledge remote site is tasked with accompanying UMKM actors offline with the aim of increasing the quality of knowledge, as well as understanding the entrepreneurial skills of UMKM actors, so they can compete with similar industries. In this case the constrains experienced. Keyword: UMKM Perpetrators, Facilitator Access to Knowladge Remote Site